THE PHENOMENON OF ONLINE PROSTITUTION THROUGH THE MI-CHAT APPLICATION IN INDRAMAYU DISTRICT - Natsir, Luthfi Faisal (Journal of Learning on History and Social Sciences, 2024)
One of the social media applications that is misused as a tool for online prostitution transactions is Mi-chat or what the general public terms the "ijo" application, online prostitution using this application has spread to urban and rural communities. In 2022, it attracted the attention of the people of Indramayu Regency that there had been a case of murder in a boarding house committed by a consumer against a sex service provider due to an argument not being in accordance with the predetermined rates. The aim of this research is to determine the phenomenon of online prostitution through the Mi-Chat application in Indramayu Regency. The method used in this research is descriptive qualitative. The results of research conducted by researchers show that the phenomenon of online prostitution, prostitution activities in general, have a place or localization for carrying out prostitution activities, but this is different from online prostitution activities, in this case, through the Mi-chat application, prospective consumers can choose prospective prostitution service providers. make direct contact via search results on your mobile device, by first downloading the application on the Playstore which is free and can be accessed by the public